Mapping the Multicoloured Inukshuk in Canada's Multicultural Landscape - Harris, Rachel (2009)
My paper is a study of the sixty year history of the inukshuk’s cultural appropriations from humanoid-rock-formation to Canadian-Nunavut-Olympics icon. It traces the inukshuk variant in Canadian visual culture from its Inuit source in southern Canada to its cultural appropriations in popular culture, state insignia and in the monuments and stone formations that thread the Canadian wilderness into an east to west tundra simulacra. It focuses on issues of cultural appropriation and Canadian identity representation, which are significant for current cultural property relations between nation-state, the Fourth World and the Olympics. Comparing the interrelationship between the references to Canada’s northern landscape in the Vancouver 2010 Olympics logo, known as Ilanaaq, and the Nunavut and Canadian flags’ foregrounds the complexity of the cultural property debate. I posit that the visual pairing of the inukshuk and the maple leaf in the design of Ilanaaq demonstrates how the idea of Canada-as-North has evolved into a multicultural tundra simulacrum. This evolution has occurred in tandem with official recognition of Inuit voice in the formation of Nunavut. I come to the assertion that in the image of Ilanaaq the essentialist division between Aboriginal and non-Aboriginal Canadians nevertheless persists in an idea of Canada as multicultural nation. Unless Ilanaaq’s likeness to the Nunavut flag provides an alternative reading for the Canadian-Olympics icon as reapreappropriated symbol of Inuit self-representation, the VANOC logo is nothing more than a problematic form of Canadian identity representation. This research was supported by the Social Sciences and Humanities Research Council of Canada.